New data on bats from Dire Dawa region, eastern Ethiopia, with the first record of Rhinopoma microphyllum in the country. Issue 41 (10th November 2019) - Benda, P.; Kasso, M.; Nicolas, V.; Pleurdeau, D.; Stoetzel, E.; Workalemahu, S.; Bekele, A.; Denys, C.
ABSTRACT: A small collection of bats composed of six species from Dire Dawa area, eastern Ethiopia, is presented. Besides three species previously known in the region, Rousettus aegyptiacus, Epomophorus minimus and Chaerephon pumilus, three bats were newly documented from the area, Rhinopoma microphyllum, R. cystops and Scotophilus leucogaster. R. microphyllum is here reported for the first time in Ethiopia. From molecular genetic comparisons Ethiopian R. cystops belongs to the Arabian subspecies lineage R. c. arabium, previously unknown from the African continent, raising interesting biogeographic questions.